1, 2, 3-Triazoles derived from olanzapine: their synthesis via an ultrasound assisted CuAAC method and evaluation as inhibitors of PDE4B. Issue 115 (3rd November 2015) - Nallapati, Suresh Babu; Sreenivas, B. Yogi; Bankala, Ramudu; Parsa, Kishore V. L.; Sripelly, Shivashankar; Mukkanti, K.; Pal, Manojit
Abstract : An ultrasound assisted CuAAC method afforded novel 1, 2, 3-triazoles derived from olanzapine as inhibitors of PDE4B. Abstract : The antipsychotic drug olanzapine which does not inhibit PDE4 can be converted into the inhibitor of PDE4B via linking its N -10 position with an appropriately N -substituted 1, 2, 3-triazole moiety through a methylene linker. All these compounds were conveniently prepared by a CuAAC method under ultrasound irradiation at room temperature and evaluated for their PDE4 inhibitory potential in vitro . Three of them were identified as selective inhibitors of PDE4B (IC50 ∼ 5–6 μM) over PDE4D. Overall, the present research reports one of the few examples of an ultrasound assisted CuAAC method used in medicinal chemistry.